Mechanisms of glycosylation and sulfation in the Golgi apparatus: evidence for nucleotide sugar/nucleoside monophosphate and nucleotide sulfate/nucleoside monophosphate antiports in the Golgi apparatus membrane. - Capasso, J M (1984)
The mechanism of translocation in vitro of sugar nucleotides and adenosine 3'-phosphate 5'-phosphosulfate (PAPS) into the lumen of rat liver Golgi apparatus vesicles has been studied. It has been previously shown that the Golgi apparatus membrane has specific carrier proteins for PAPS and sugar nucleotides. We now report that translocation of the above nucleotide derivatives across Golgi membranes occurs via a coupled equimolar exchange with the corresponding nucleoside monophosphates. An initial incubation of Golgi vesicles with GDP-fucose radiolabeled in the guanidine ring resulted in accumulation within the lumen of radiolabeled GMP. Exit of GMP from these vesicles was specifically dependent on the entry of (additional) GDP-fucose into the vesicles (GDP-mannose and other sugar nucleotides had no effect). GDP-fucose-stimulated exit of GMP was temperature dependent, was blocked by inhibitors of GDP-fucose transport, such as 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid, and appeared to be equimolar with GDP-fucose entry. Preliminary evidence for specific, equimolar exchange of CMP-N-acetylneuraminic acid with CMP, PAPS with 3'-AMP, and UDP-galactose and UDP-N-acetylglucosamine with UMP was also obtained. These results strongly suggest the existence of different antiport proteins within the Golgi membrane that mediate the 1:1 exchange of sugar nucleotides or PAPS with the corresponding nucleoside monophosphate. Such proteins may have a regulatory role in glycosylation and sulfation reactions within the Golgi apparatus.